Evaluation of 389 patients following free-flap lower extremity reconstruction with respect to secondary refinement procedures - Kotsougiani-Fischer, Dimitra; Bigdeli, Amir Khosrow; Kremer, Thomas; Kneser, Ulrich; Harhaus-Wähner, Leila (Microsurgery, 2018)
Introduction Primary functional and aesthetic results after free-flap salvage of lower extremities are occasionally suboptimal. The objective of this study was to identify predictors for secondary refinement procedures such as liposuction, dermolipectomy, or direct excision. In addition, patient-reported long-term satisfaction with the final reconstructive result was analyzed. Patients and Methods All patients undergoing free-flap lower extremity salvage between January 2011 and July 2015 were included in a comparative study. The patients of cohort 1 had no secondary refinement procedures, while those of cohort 2 had one or more procedures. The patient data, intraoperative characteristics, and postoperative course were reviewed. To assess the level of satisfaction, the patients were surveyed. Results Of the 389 patients included, 54 (13.9%) were identified with 1-3 secondary refinement procedures with an uneventful postoperative course. The most common procedure was surgical debulking (56.8%). The comparison of both cohorts revealed a statistical significance for patient's age (P < .01), gender (P = .02), ASA-score (P < .01), and localization (P < .01). Predictors for secondary refinement procedures were young age (<50 years), female gender, absence of comorbidities, and defects located at the feet or ankle. Overall patient satisfaction was negatively correlated with the number of secondary procedures performed. Patient-reported satisfaction with the overall (P < .01) and cosmetic (P = .02) result increased significantly with age. Conclusion Secondary refinement procedures after successful free-flap lower extremity reconstruction are safe and not uncommon. Detailed information about the likelihood of secondary operations and the various techniques available should be part of the patient education to increase patient satisfaction and form realistic expectations.